Point last seen - Dodd, Christina (HQN, 2022)
"LIFE LAST SEEN. When you've already died, there should be nothing left to fear... When Adam Ramsdell pulls Elle's half-frozen body from the surf on a lonely California beach, she has no memory of what her full name is and how she got those bruises ringing her throat. GIRL LAST SEEN. Elle finds refuge in Adam's home on the edge of Gothic, a remote village located between the steep lonely mountains and the raging Pacific Ocean. As flashes of her memory return, Elle faces a terrible truth--buried in her mind lurks a secret so dark it could get her killed. POINT LAST SEEN. Everyone in Gothic seems to hide a dark past. Even Adam knows more than he will admit. Until Elle can unravel the truth, she doesn't know who to trust, when to run and who else might be hurt when the killer who stalks her nightmares appears to finish what he started..."--Dust jacket flap.